Rapid and specific immunoPET imaging of Nectin-4 in gastric cancer and non-small cell lung cancer using [64Cu]Cu-NOTA-EV-F(ab')2. - Huang, Wenpeng; Sun, Xinyao; Li, Xiaoyan; Hsu, Jessica C.; Qiu, Yongkang; DeLuca, Molly C.; Engle, Jonathan W.; Li, Liming; Lu, Jun; Wang, Tianyao; Kang, Lei; Cai, Weibo (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: This study aimed to develop and evaluate [64Cu]Cu-NOTA-EV-F(ab')2 as a rapid and specific immunoPET imaging probe targeting Nectin-4 in gastric cancer (GC) and non-small cell lung cancer (NSCLC). Materials and methods: F(ab')2 fragments were generated from enfortumab vedotin (EV) using IdeS protease and conjugated with p-SCN-Bn-NOTA for radiolabeling with 64CuCl2. The radiochemical yield was 85.40 ± 2.43% (n = 5). In vitro binding affinity and specificity were assessed via flow cytometry and cell uptake assays using Nectin-4-positive (NCI-N87, H1975) and Nectin-4-low (HGC-27, H520) cell lines. In vivo PET imaging and biodistribution studies were conducted in murine models of GC and NSCLC to evaluate tumor targeting efficiency and tracer pharmacokinetics. Results: [64Cu]Cu-NOTA-EV-F(ab')2 demonstrated rapid tumor accumulation, with peak uptake observed at 4 h post-injection (10.23 ± 0.70%ID/g in NCI-N87 tumors, 3.03 ± 0.35%ID/g in HGC-27, 11.56 ± 1.12%ID/g in H1975, 2.77 ± 0.47%ID/g in H520). Compared to full-length EV, the tracer exhibited faster blood clearance and reduced off-target uptake. Blocking with excess EV-F(ab')2 significantly reduced subsequent tumor uptake (6.27 ± 0.49%ID/g in NCI-N87, P = 0.0029; 5.23 ± 0.31%ID/g in H1975, P = 0.00074), confirming Nectin-4 specificity. Ex vivo biodistribution analysis supported high tumor retention consistent with in vivo imaging findings. Conclusions: [64Cu]Cu-NOTA-EV-F(ab')2 offers rapid, specific, and high-contrast immunoPET imaging of Nectin-4-expressing tumors in GC and NSCLC models, highlighting its potential as a non-invasive diagnostic tool for Nectin-4-targeted cancer imaging.